Thoracic Epidural Anesthesia Facilitating Upper Abdominal Surgery in the Presence of Malignant Pleural Effusion and Hepatic Metastases: A Case Report - Faisal Irwanda; Andre Azhar; Dino Irawan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Upper abdominal surgery in patients with advanced metastatic cancer, particularly with significant pulmonary and hepatic involvement, presents substantial perioperative challenges. Malignant pleural effusion (MPE) and hepatic metastases compromise cardiorespiratory reserve, increasing the risks associated with general anesthesia and surgical stress. Thoracic epidural anesthesia (TEA) offers potential benefits by providing effective analgesia, reducing pulmonary complications, and attenuating the surgical stress response. Case presentation: We report the case of a 65-year-old male patient with metastatic breast cancer involving the lungs, liver, and spine, complicated by recurrent malignant pleural effusion. He presented with dyspnea and abdominal pain, requiring a laparotomy for liver biopsy to guide further oncological management. Given his ASA III status, significant pulmonary compromise (pre-operative SpO2 93-94% on room air, effusion requiring drainage), and the nature of the surgery, TEA was chosen as the primary anesthetic technique. An epidural catheter was successfully placed at the T9-T10 interspace, achieving a T4 sensory block using ropivacaine 0.5%. The laparotomy and liver biopsy proceeded with stable intraoperative hemodynamics and adequate surgical conditions. Conclusion: TEA provided effective anesthesia and analgesia for upper abdominal surgery in this high-risk patient with extensive metastatic disease and compromised pulmonary function. This approach facilitated the procedure while maintaining hemodynamic stability and avoiding the potential respiratory complications associated with general anesthesia and tracheal intubation. TEA should be considered a viable anesthetic option in carefully selected high-risk patients undergoing abdominal oncological surgery.